A conceptual blending analysis of a metaphorical advertisement: applications in elt - Sá, Elisa Mattos de (BELT - Brazilian English Language Teaching Journal, 2017)
Advances in Cognitive Linguistics have focused on the centrality of meaning and conceptual structure in human language (Evans & Green, 2006; Geeraerts, 2006), placing phenomena such as metaphor as central to human cognition (Lakoff, 2006; Lakoff & Johnson, 1980). This paper analyzes the process of meaning construction of a metaphorical print advertisement in which cognitive operations of conceptual integration (cf. Fauconnier & Turner, 2002) can be mapped through the interplay between verbal and nonverbal language. Seeing that adverts can provide learners with real-life communicative opportunities for language development due to their up-to-date language, cultural-bound content, and creative discourse techniques (Mishan, 2005; Picken, 2000; 1999), this paper additionally provides four pedagogical applications of the chosen advertisement in English Language Teaching, drawing on the principles of the theoretical framework presented.